2016
DOI: 10.4137/nmi.s39043
|View full text |Cite
|
Sign up to set email alerts
|

Role of n-3 Polyunsaturated Fatty Acids and Exercise in Breast Cancer Prevention: Identifying Common Targets

Abstract: Diet and exercise are recognized as important lifestyle factors that significantly influence breast cancer risk. In particular, dietary n-3 polyunsaturated fatty acids (PUFAs) have been shown to play an important role in breast cancer prevention. Growing evidence also demonstrates a role for exercise in cancer and chronic disease prevention. However, the potential synergistic effect of n-3 PUFA intake and exercise is yet to be determined. This review explores targets for breast cancer prevention that are commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 145 publications
1
8
0
Order By: Relevance
“…For example, the decreased expression of the enzyme involved in fatty acids (FAs) elongation influenced cell migration, cell–cell interactions, and MMP’s synthesis. However, this is not an entirely unexpected result, as previously, it was shown that omega-3 and omega-6 PUFAs, the products of ELOVL5 activity, affect the proliferation, migration, and invasion of cancer cells in vitro ( Chamras et al, 2002 ; Yun et al, 2014 ; Gonzalez-Reyes et al, 2017 ; Huang et al, 2017 ) and that dietary omega-3 FAs reduce the risk of BC development, as well as the risk of its relapse ( Abdelmagid et al, 2016 ; Playdon et al, 2017 ; Romieu et al, 2017 ; Shapira, 2017 ). Still, there is no simple explanation for these results, since the effect of PUFAs on cellular processes is multifaceted.…”
Section: Discussionsupporting
confidence: 66%
“…For example, the decreased expression of the enzyme involved in fatty acids (FAs) elongation influenced cell migration, cell–cell interactions, and MMP’s synthesis. However, this is not an entirely unexpected result, as previously, it was shown that omega-3 and omega-6 PUFAs, the products of ELOVL5 activity, affect the proliferation, migration, and invasion of cancer cells in vitro ( Chamras et al, 2002 ; Yun et al, 2014 ; Gonzalez-Reyes et al, 2017 ; Huang et al, 2017 ) and that dietary omega-3 FAs reduce the risk of BC development, as well as the risk of its relapse ( Abdelmagid et al, 2016 ; Playdon et al, 2017 ; Romieu et al, 2017 ; Shapira, 2017 ). Still, there is no simple explanation for these results, since the effect of PUFAs on cellular processes is multifaceted.…”
Section: Discussionsupporting
confidence: 66%
“…Collectively, the results indicate that the low 22:6n-3 EtnPls level observed in BC could increase the susceptibility of cells to the overactivity of ACC by reducing the expression of BRCA proteins and reducing the ability of the cell to counteract this overactivity by reducing cholesterol efflux. Accordingly, n-3 supplementation and exercise are complementary peroxisomal stimulators and have value in BC prevention [39].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 ( n -3) polyunsaturated fatty acids (PUFAs) have anti-inflammatory properties and are thought to be critical in breast cancer prevention [100]. n -3 PUFAs can be found in foods like fish, fish oil, marine sources, flaxseed, nuts, and eggs [99].…”
Section: Dietary Factors and Nutrition In Breast Cancer Riskmentioning
confidence: 99%
“…Insights into mechanisms that may contribute to the beneficial health effects of n -3 PUFAs can be gleaned by reviewing recent work by Kiecolt-Glaser et al [106], showing that n -3 PUFAs supplementation positively impacted cell aging, thereby highlighting how inflammation, oxidative stress, and immune cell aging—which appear to be important mechanisms prior to disease onset—that may be ameliorated through nutritional interventions. Among women, n -3 PUFA intake has been found to be inversely associated with breast cancer risk [99, 100, 107, 108] and breast cancer mortality [103, 104]. Mechanisms underlying the beneficial effects of higher consumption of marine n -3 fatty acids in terms of lowering breast cancer risk might be attributed to the growth-inhibitory, pro-apoptotic, or anti-angiogenic effects of n -3 fatty acids that can be found in fish [100, 103].…”
Section: Dietary Factors and Nutrition In Breast Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation